2023
DOI: 10.3389/fphy.2023.1150671
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved infrared difference spectroscopy in cells: Response of the basic region leucine zipper of aureochrome

Abstract: Aureochromes are light, oxygen, voltage (LOV) proteins and central blue-light receptors in algae acting as light-gated transcription factors. The C-terminal LOV domain mediates blue-light recognition and the basic region leucine zipper (bZIP) domain binds a specific DNA motif as effector. LOV domains from aureochromes have been successfully applied in optogenetic tools. The light-induced response of aureochromes has been studied by a variety of biophysical techniques, but the mechanism of signal progression fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 62 publications
(79 reference statements)
0
4
0
Order By: Relevance
“…7 ). Specifically, it has been reported that under BL illumination, the Jα-helix influences the dimerizations of the bZIP domains, confirming that the bZIP dimer cannot be formed without this unfolding of the Jα-helix in BL conditions ( Herman et al , 2013 ; Goett-Zink et al , 2023 ) and, further, the A'α-helix influences the LOV–LOV domain dimerization ( Herman and Kottke, 2015 ; Goett-Zink et al , 2023 ). Consequently, these structural changes in the LOV domain affect the bZIP domain’s flexibility and bZIP dimerization capacity, influencing PtAUREO1a’s gene regulation property.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…7 ). Specifically, it has been reported that under BL illumination, the Jα-helix influences the dimerizations of the bZIP domains, confirming that the bZIP dimer cannot be formed without this unfolding of the Jα-helix in BL conditions ( Herman et al , 2013 ; Goett-Zink et al , 2023 ) and, further, the A'α-helix influences the LOV–LOV domain dimerization ( Herman and Kottke, 2015 ; Goett-Zink et al , 2023 ). Consequently, these structural changes in the LOV domain affect the bZIP domain’s flexibility and bZIP dimerization capacity, influencing PtAUREO1a’s gene regulation property.…”
Section: Discussionmentioning
confidence: 79%
“…As it is postulated that AUREOs evolved from a non-light-sensitive form to a light-sensitive form ( Khamaru et al , 2022a , Preprint), gene regulation of PtAUREO1a in the absence of BL illumination (RL or dark) might be indicative of its ancestry, and PtAUREO1a may have further evolved to serve comprehensive roles utilizing the sensory domain. Indeed, several studies have confirmed that the conformational changes of PtAUREO1a are influenced by BL illumination, specifically due to the changes in structure of the LOV domain ( Herman et al , 2013 ; Banerjee et al , 2016b ; Heintz and Schlichting, 2016 ; Goett-Zink et al , 2023 ). Although it is confirmed that PtAUREO1a can dimerize in the dark ( Banerjee et al , 2016b ; Heintz and Schlichting, 2016 ), BL induces the LOV domain to disassociate from the bZIP domain and induces a structural change of flanking helices of the LOV domain ( Goett-Zink et al , 2023 ) ( Fig.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations